2008
DOI: 10.4088/pcc.v10n0503
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety and Tolerability of Rivastigmine in Patients With Alzheimer's Disease Switched From Donepezil

Abstract: For patients not tolerating or not responding to donepezil, treatment with rivastigmine was safe and well tolerated for at least 52 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…After excluding 4,324 papers after title and abstract review, 264 full‐text articles were examined, and 31 studies were \ included in the systematic review with meta‐analysis (22 longitudinal studies without a control group; 9 cohort studies with a control group) (Supplementary Figure S1). Seven of those were open‐label studies . The 22 longitudinal studies included a total of 34 independent cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding 4,324 papers after title and abstract review, 264 full‐text articles were examined, and 31 studies were \ included in the systematic review with meta‐analysis (22 longitudinal studies without a control group; 9 cohort studies with a control group) (Supplementary Figure S1). Seven of those were open‐label studies . The 22 longitudinal studies included a total of 34 independent cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of those were open-label studies. [20][21][22][23][24]33,37 The 22 longitudinal studies included a total of 34 independent cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, memantine has been prescribed alone or in combination with other cognitive drugs such as donepezil (Aricept ® ), rivastigmine (Exelon ® ) and galantamine (Razadyne ® ) as well as anti-psychotic drugs [ 6 , 7 ]. It has been reported that no drug-drug interaction between memantine and donepezil, rivastigmine and galantamine was observed [ 8 , 9 , 10 ]. However, it may interact with other N -methyl- d -aspartate receptor ligands such as dextromethorphan, ketamine and phencyclidine and anti-psychotic drugs such as amantadine and dopamine antagonists [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mean drugplacebo differences, at end point for the groups receiving 5 mg/d and 10 mg/d of donepezil hydrochloride were, respectively, 2.5 and 3.1 units for the ADAS-cog (11,12). Results from a Cochrane review suggest that donepezil results in statistically significant improvements for both 5 and 10 mg/day at 24 weeks compared with placebo on the ADAS-cog, with a 2.01 point and a 2.80 point reduction, respectively (9).…”
Section: Donepezilmentioning
confidence: 99%